Mechanical properties of layered laminated woven bamboo gigantochloa scortechinii/epoxy composites - Rassiah, Kannan; Megat Ahmad, M. M. H.; Ali, Aidy; Abdullah, Abd Halid; Nagapan, Sasitharan (Springer Nature, 2018)
This study investigated the application of bamboo as a natural composite, in which its potential as a composite material had been examined for 2–6 layers. In precise, the woven bamboo (BW) formed the culm fiber composite with an average of 0.5 mm thickness and 5.0 mm width strip. In addition, this study looked into a specific type of bamboo species known as Gigantochloa Scortechinii (Buluh Semantan), which can be found in Malaysia. This laminated plain BW, which had been reinforced with epoxy (EP), was developed by applying the hand lay-up technique. After that, the specimens were characterized via mechanical analyses, for instance, tensile, flexural, hardness, and impact tests. As a result, the 2-layer BW had displayed rather excellent results chiefly due to the incorporation of epoxy composite, although this is exceptional hardness value.